Development of Kado Ragam with Tri Hita Karana Content to Enhance Learning Activity and Learning Outcomes in Pancasila Education for Grade V Elementary School Students - I Nyoman Sudianta; Dewa Bagus Sanjaya; I Wayan Suastra (MASI Mandiri Edukasi, 2026)
This research aims to produce media, determine the validity and practicality of the media, and describe the effectiveness of developing domino card media on diversity (kado ragam) with Tri Hita Karana content to increase activity and learning outcomes in Pancasila Education. Development research type using the ADDIE model. The study subjects were students from SD N Renon Denpasar, comprising 30 students in class VA and 32 in class VB, along with four teachers serving as practitioners. The data collection methods are questionnaires and tests. The research instruments include media, materials, practicality, learning activities, and multiple-choice tests. The learning activity instrument was tested for validity and reliability. The learning outcome instrument was tested for validity, reliability, discrimination, and difficulty. Data analysis was performed using percentages, one-way ANOVA, and multivariate tests. The research results show that: Various gifts are presented in printed form, with media validity at 92.3%, material at 95.39%, and practicality at 86.05, which falls into the very practical category. The effectiveness results show statistical values for Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root, with an F-statistic of 83.280 and a significance level of 0.001. This value is smaller than the significance level of 0.05 (p < 0.05). Conclusion: The Kado Ragam media simultaneously influences Tri Hita Karana content on student activity and learning outcomes.